2011
DOI: 10.1074/jbc.m110.192526
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the PIP2 Sensor of TRPV1 Ion Channels

Abstract: Although a large number of ion channels are now believed to be regulated by phosphoinositides, particularly phosphoinositide 4,5-bisphosphate (PIP2), the mechanisms involved in phosphoinositide regulation are unclear. For the TRP superfamily of ion channels, the role and mechanism of PIP2 modulation has been especially difficult to resolve. Outstanding questions include: is PIP2 the endogenous regulatory lipid; does PIP2 potentiate all TRPs or are some TRPs inhibited by PIP2; where does PIP2 interact with TRP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
145
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(151 citation statements)
references
References 36 publications
6
145
0
Order By: Relevance
“…The TRPV1 CTD is also implicated in cap-saicin-induced desensitization through its ability to bind calmodulin (CaM) (17)(18)(19). The "TRP domain" within the TRPV1 CTD was also suggested to be involved in capsaicin-induced desensitization (20,21). Given the fact that there are regions and residues of TRPV1 that are distinctly involved in activation by capsaicin and heat and that capsaicin and heat desensitize TRPV1 through apparently distinct mechanisms, we hypothesized that capsaicin and heat desensitize TRPV1 through distinct segments within the CTD.…”
Section: Transient Receptor Potential Vanilloid 1 (Trpv1)mentioning
confidence: 99%
“…The TRPV1 CTD is also implicated in cap-saicin-induced desensitization through its ability to bind calmodulin (CaM) (17)(18)(19). The "TRP domain" within the TRPV1 CTD was also suggested to be involved in capsaicin-induced desensitization (20,21). Given the fact that there are regions and residues of TRPV1 that are distinctly involved in activation by capsaicin and heat and that capsaicin and heat desensitize TRPV1 through apparently distinct mechanisms, we hypothesized that capsaicin and heat desensitize TRPV1 through distinct segments within the CTD.…”
Section: Transient Receptor Potential Vanilloid 1 (Trpv1)mentioning
confidence: 99%
“…Among them, Ca 2+ ions are important because not only the effects are substantial and rapid but also Ca 2+ influx through activated channels provides a powerful physiological negative feedback mechanism 10 . Modulation of channel activity by intracellular Ca 2+ is mediated by multiple mechanisms utilizing calmodulin 34,35,41,42 , Phosphorylation 43 , and PIP2 [44][45][46][47][48] . As F430_3aa and E693_8aa exhibit specific and substantial deficits in Ca 2+ -dependent desensitization, they may serve as useful tools to further investigate the allosteric coupling process between the intracellular domains and the transmembrane core domain.…”
Section: Discussionmentioning
confidence: 99%
“…Extended recordings, however, revealed that there was a substantial difference in the current decline phase. The current decline represents Ca 2+ -dependent acute desensitization, a process thought to be mediated by multiple mechanisms, including binding of Ca 2+ -calmodulin to the ankyrin-like repeat domain 34,35,41,42 , phosphorylation 43 , and binding of PIP2 to the C-terminus [44][45][46][47][48] , that allosterically modulate the stability of the open pore conformation. For the wild-type channel, as expected little desensitization was observed in the absence of Ca 2+ .…”
Section: Functional Tests Of Insertion Mutantsmentioning
confidence: 99%
“…PI(4,5)P 2 has been proposed to inhibit TRPV1 by binding to amino acids 777-820 in the distal C-terminal region (Prescott and Julius, 2003) and to activate TRPV1 by binding to the proximal C-terminal region represented by amino acids 682-725 ( Fig. 1 A, magenta; Ufret-Vincenty et al, 2011). In addition, mutations in the ankyrin repeat domains appear to abrogate PI(4,5)P 2 depletion-mediated desensitization of TRPV1, although a direct interaction between PI(4,5)P 2 and a fragment corresponding to the ankyrin selectivity.…”
mentioning
confidence: 99%
“…Based on this structure, it seems reasonable to predict that GIRK2 might display some phosphoinositide Mechanism for phosphoinositide selectivity and activation of TRPV1 ion channels the response of pain receptor neurons to noxious stimuli, disagreement about whether PI(4,5)P 2 activates or inhibits TRPV1 continues (Chuang et al, 2001;Prescott and Julius, 2003;Stein et al, 2006;Lukacs et al, 2007Lukacs et al, , 2013a; Ufret-Vincenty et al, 2011;Cao et al, 2013a,b;Senning et al, 2014). There is also disagreement about whether PI(4,5)P 2 interacts directly with TRPV1 or acts via the integral membrane protein Pirt (Kim et al, 2008;Ufret-Vincenty et al, 2011). Finally, several regions of TRPV1 have been proposed for mediating the interaction with PI(4,5)P 2 , some of which are illustrated in Fig.…”
mentioning
confidence: 99%